Colônia de Itanhenga a luta contra a lepra no Espírito Santo (1934 - 1945) - Barros, Luiz Arthur Azevedo (2014)
This dissertation aims to analyze how they were developed and implemented the actions, in the form of public health policies, to combat the spread of leprosy in the state of Espirito Santo, between 1934-1945. This period corresponds to the management of Gustavo Capanema ahead of the Ministry of Education and Health, during the Vargas Government, when there was a major restructuring of public health in Brazil, with great attention to the elimination of leprosy. The main action of these policies was the compulsory isolation of patients infected by the disease in areas identified as leprosarium or agricultural colonies for lepers. The main focus of this research is to identify and understand the reasons that led to the decision for building the Colony of Itanhenga, started in 1935 and completed in 1937, to receive the lepers of the state of Espírito Santo, how were mobilized resources for this construction and what was the involvement of the federal intervenor João Punaro Bley and civil society in this process. To achieve these goals were used different textual sources such as documents, letters and forms that belong to the personal archive of Gustavo Capanema (FGV/CPDOC); News and articles published in the newspapers of the Rio de Janeiro and Espírito Santo; books and articles by Dr. Heraclides Cesar de Souza Araujo published in the magazine "Memórias do Instituto Oswaldo Cruz"; Government reports and messages of the state of Espírito Santo.